Perbandingan Pola Kuman dan Kadar Biomarker Inflamasi Penderita Severe Pneumonia dengan Penderita Non-severe Pneumonia : [Bacterial Pattern and Inflammatory Biomarker in Severe Pneumonia Compared to Non-Severe Pneumonia Patient] - Daniel Maranatha; Mawardi Mawardi (Faculty of Medicine Universitas Airlangga, 2019)
Background: Severe pneumonia is still a serious problem with high mortality rate. The cause of severe pneumonia due to high inflammation or different microbial pattern compared to non-severe pneumonia is still unknown. Methods: An analytic observational study with cross-sectional design was performed in patients with severe pneumonia and non-severe pneumonia treated in intensive care unit (ICU), intensive observation room (ROI), and all inpatient wards of Dr. Soetomo General Hospital Surabaya for a period of 1 year from September 2017 to September 2018. Patients with pneumonia accompanied by active pulmonary tuberculosis (TB), lung tumors, and acute infections other than pulmonary organs were excluded from this study. All study subjects were taken for sputum samples for aerobic sputum culture and blood samples for biomarker examination of C-reactive protein (CRP) and procalcitonin (PCT). Results: The total subjects were 64. Mean value of CRP and PCT levels severe pneumonia was 143.8 mg/L and PCT levels 23.1 ng/ml, respectively. Mean value of CRP and PCT levels non-severe pneumonia was 75.0 mg/L and PCT level 8.08 ng/ml, respectively. There was a significant difference in CRP and PCT levels of severe pneumonia and non-severe pneumonia patients (p < 0.05), whereas no meaningful difference in microbial patterns in both groups. Conclusion: Since inflammation responses of severe pneumonia were more massive than nonsevere patients, it will produce higher CRP and PCT levels.